2020
DOI: 10.1590/1806-9282.66.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness degree of ankle range of motion in diabetic patients with atypical amputation

Abstract: SUMMARY In diabetics, foot deformities are risk factors that increase the risk of amputation as a result of developing ulcers. However, knowledge of the influence of plantar stiffness is still limited. The main objective was to describe connections between the degree of stiffness of the ankle, atypical amputation, and the Foot Posture Index (FPI). METHODS 62 diabetic patients, 58 with type 2 and 4 with type 1 (average age 63.35 years) were included. Records of foot deformities were included; A range of motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
0
13
3
2
Order By: Relevance
“…Furthermore, Eduardo et al reported that patients with diabetes who had minor amputations had an average ankle dorsi exion angle of 9.6° [34] The mean dorsi exion angle in the reamputation group in this study was 2.6°, which was very low compared to that reported in previous studies.…”
Section: Discussioncontrasting
confidence: 76%
“…Furthermore, Eduardo et al reported that patients with diabetes who had minor amputations had an average ankle dorsi exion angle of 9.6° [34] The mean dorsi exion angle in the reamputation group in this study was 2.6°, which was very low compared to that reported in previous studies.…”
Section: Discussioncontrasting
confidence: 76%
“…Furthermore, Eduardo et al reported that patients with diabetes who had minor amputations had an average ankle dorsi exion angle of 9.6° [34]. The mean dorsi exion angle in the re-amputation group in this study was 2.6°, which was very low compared to that reported in previous studies.…”
Section: Discussioncontrasting
confidence: 72%
“…Moreover, the foot-care instruments or methods used in previous studies of older people in the community with diabetes were not adequately suited to this population. In future studies, a different study design may be used based on resources presented in previous studies (Navarro-Flores et al, 2018, 2020a, 2020c, 2021Sánchez-Gómez et al, 2020;Simón-Pérez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%